MACROMYCETES OF NAGORNO-KARABAKH. REPORT 1. AGARICOID MACROMYCETES (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
For the first time special researches of macroscopic fungi of Republic of Nagorno-Karabach are accomplished. In this work is given the taxonomic analysis of distribution of systematic categories of Agaricoid Basidiomycetes. The nomenclature and systematic belonging of taxon is specified in compliance with the modern classification systems. The list of 67 species agaricoidal fungi is given, which are discovered, in the investigated area.
Keywords: macroscopic fungi; taxonomic analysis; Agaricoid Basidiomycetes; taxon